Építőipari kockázatok rétegei = Analysis of construction risks of layer - Cserpes, Imre; Szabó, József (International Journal of Engineering and Management Sciences, 2017)
Risk and uncertainty are subjects of philosophic and theoretic discussions long time ago. Both concepts have the intention that nature and effects of future happenings have to be analyzed and forecasted. Difference is though that analysis is possible by different means. Uncertainty is frightening and hard to be analyzed. On the other hand, risk is better served by data, easier to find a methodology that makes it a more acceptable and manageable object. Theoretic part of the article states that risk and uncertainty entitle a risk spectrum. The next statement is that this spectrum has layers piled on one on the other, from which risk and uncertainty are the ones on the sides.